On the Derivation of the Equations of Gravitation and Electrodynamics from the Generalized Least Action Principle and the Nonrelativistic Models of the Universe - Vedenyapin, V.V.; Fimin, N.N.; Russkov, A.A.; Voronina, M.Yu. (Journal of Vibration Testing and System Dynamics, 2026)
Of the Maxwell and Einstein equations in the framework of the Vlasov–Maxwell–Einstein equations from the classical, but more general principle of least action. The resulting derivation of the Vlasov–type equations gives the Vlasov–Einstein equations different from those proposed earlier. A method is proposed for the transition from kinetic equations to hydrodynamic–type equations. In the case of Hamiltonian mechanics, the transition to the Hamilton–Jacobi equation from the hydrodynamic consequences of the Liouville equation is possible, as was done already in quantum mechanics. Thus, in the nonrelativistic case, we obtain the Milne–McCrea–type solutions.